"Jihad": What's Happening with this Virtue? - Milla, Mirra; El Hafiz, Subhan; Rohman, Izza; Edison, Rizki (My University, 2015)
"Jihad" for Muslim is a virtue, it’s learned from generation to generation. But nowadays we can see that this virtue has had different interpretations in society, from peaceful to terrorism. This research will be conducted in Indonesia, the place that is known as one of the biggest Islamic communities in the world. The primary research questions are (i) how jihad as a virtue have been shared as an idea in society, and (ii) how motivation to implement this virtue can be very different one to another (iii) what are psychosocial factors that give contribution in implement-ing of these virtue. The study will be conducted in three of study with different methods. The first study aims to explain the variety of the virtue of Jihad that can be derived from Islamic lit-erature. The second study is qualitative-comparative, using a social representation approach, this study will explain the personal and social pattern in understanding of different representations of virtue Jihad and the implementation. The result from the second study will be tested in la-boratory with experimental design which aims to test the different reactions of the brain regard-ing the motivation difference of jihad between person's moral obligatory or emotional inclina-tion on some variation differences group of jihad interpretation. Using Electrical Capacitance Volume Tomography (ECVT) we will record how brain will react in specific situation. This re-search will integrate three disciplines: humanities (theology), social science (psychology and so-ciology), and natural science (physiology and neuroscience) all studying the same virtue, Jihad. The research expected outcomes are to explain the variety of the virtue of Jihad that can be de-rived from Islamic literature, and to describe the representation of virtue of Jihad and its im-plementation on individual level and different type of group in Islamic community in Indonesia.
Keywords: Philosophy; Religion, Philosophy of.